AN ANALYSIS OF CONJUNCTION ERRORS IN RECOUNT TEXT: A Study at the 10th Grade of SMAN 1 Gerung - Muhammad Rizal Waldi; Boniesta Zulandha Melani; Husnul Lail; Lalu Nurtaat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Grammar is a common challenge in English writing, particularly among 10th-grade high school students, where conjunction errors in recount texts are prevalent. This study investigates the most frequent types of conjunction errors and the factors causing them. Using a qualitative descriptive approach, data were collected through writing tests, content analysis, and interviews with students of SMAN 1 Gerung. The study identified 32 errors in students' recount texts: 78% in coordinating conjunctions, 22% in subordinating conjunctions, and no errors in correlative conjunctions. Common errors included unnecessary conjunctions, ambiguity, and inappropriate conjunctions for context, which disrupted sentence coherence. Interviews revealed that conjunction errors stemmed from students' lack of understanding, forgetfulness, and insufficient teaching at school. While some students knew the function of conjunctions, others lacked basic awareness or had not been adequately instructed, particularly within the school curriculum. The findings highlight the importance of targeted teaching strategies, practice, and feedback to improve students' conjunction usage. This study underscores the need for explicit instruction and regular training in conjunctions to enhance recount texts' clarity and organization. Teachers should provide detailed explanations and constructive feedback, while students are encouraged to engage in self-editing and structured exercises. The results offer valuable insights for educators and learners to address conjunction errors and improve writing proficiency in English.